2014
DOI: 10.1016/j.crohns.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-cell KV1.3 potassium channel correlates with pro-inflammatory cytokines and disease activity in ulcerative colitis

Abstract: Background and aims Potassium channels, KV1.3 and KCa3.1, have been suggested to control T-cell activation, proliferation, and cytokine production and may thus constitute targets for anti-inflammatory therapy. Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by excessive T-cell infiltration and cytokine production. It is unknown if KV1.3 and KCa3.1 in the inflamed mucosa are markers of active UC. We hypothesized that KV1.3 and KCa3.1 correlate with disease activity and cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…In the human small intestine mucosa they are expressed in Paneth cells (128), probably contributing to the release of antimicrobial peptides (10), and intraepithelial leukocytes (128), where they participate in proinflammatory processes. In fact IK are, alongside K v 1.3 (73), crucial for T cell activation and proliferation: they keep an electrical gradient that allows Ca 2ϩ influx, which is a required step for the translocation of the nuclear factor of activated T cells (NFAT) to the nucleus, ultimately resulting in cytokine secretion and T cell proliferation (20,62). Given that IBD is a T cell-driven disease, it is unsurprising that inhibition of lymphocytic IK channels reduces inflammation and colitis manifestations, and therefore IK blockade has received considerable attention as a potential therapeutic target (38,53,106,132 …”
Section: K ϩ Channelsmentioning
confidence: 99%
“…In the human small intestine mucosa they are expressed in Paneth cells (128), probably contributing to the release of antimicrobial peptides (10), and intraepithelial leukocytes (128), where they participate in proinflammatory processes. In fact IK are, alongside K v 1.3 (73), crucial for T cell activation and proliferation: they keep an electrical gradient that allows Ca 2ϩ influx, which is a required step for the translocation of the nuclear factor of activated T cells (NFAT) to the nucleus, ultimately resulting in cytokine secretion and T cell proliferation (20,62). Given that IBD is a T cell-driven disease, it is unsurprising that inhibition of lymphocytic IK channels reduces inflammation and colitis manifestations, and therefore IK blockade has received considerable attention as a potential therapeutic target (38,53,106,132 …”
Section: K ϩ Channelsmentioning
confidence: 99%
“…Application of selective blockers of the IKCa1 and Kv1.3 potassium channels is a possible new target for autoimmune therapy [21], and in a colitis murine model they already proved to be effective and fairly selective for the over-activated cell types [22]. In our study we could justify that both MGTX and TRAM has the potential to lower the increased calcium influx in Th2 cells nearly to the level observed in healthy individuals in case of the conventionally treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Patch-clamp studies revealed that the channels play crucial roles in facilitating the calcium influx necessary to trigger the lymphocyte activation and proliferation [11, 12]. In pathological conditions, such as in chronic kidney disease (CKD) or inflammatory bowel disease (IBD), the channels were overexpressed in proliferating lymphocytes within the inflamed kidneys or intestines, and the over-activation of the channels largely contributed to the progression of the diseases [1315]. Previously, we demonstrated in an animal study that the overexpression of Kv1.3-channels in lymphocytes was deeply associated with their in situ proliferation in kidneys and the progression of chronic renal failure (CRF) [13].…”
Section: Involvement Of Lymphocyte Kv13-channels In Chronic Inflammamentioning
confidence: 99%